2020
DOI: 10.1111/dth.13459
|View full text |Cite
|
Sign up to set email alerts
|

Peeling with 70% glicolic acid followed by 5% 5‐fluorouracil as well as 5% 5‐fluorouracil cream are effective methods for the treatment of actinic keratoses on upper limbs: A randomized clinical trial

Abstract: The 5% 5‐fluorouracil (5‐FU) cream, considered the gold standard topical treatment, and peeling using 70% glycolic acid (GA) followed by 5% 5‐FU are methods for the treatment of actinic keratoses (AKs). However, the comparison of these two treatments had not yet been described and therefore was the objective of this study. A randomized clinical trial, intrapatient study in which 17 patients received a type of treatment in the right and left upper limb with 5% 5‐FU cream (twice daily) or a peeling application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Regarding the treatment of AK in the upper limbs, a self-controlled clinical trial compared the use of 5% 5-FU cream twice a day in two 15-day cycles separated by a 15-day break versus four fortnightly sessions of 70% glycolic acid peeling + 5% 5-FU solution, indicating an 85.7% reduction in the number of AK in the limbs treated with 5-FU cream. 24 The smaller sample size of the aforementioned study, the treatment area including the hands, as well as the different doses, which may interfere with adherence to treatment, are characteristics that may explain the slightly favorable difference in relation to the 75% reduction in AK count found in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…Regarding the treatment of AK in the upper limbs, a self-controlled clinical trial compared the use of 5% 5-FU cream twice a day in two 15-day cycles separated by a 15-day break versus four fortnightly sessions of 70% glycolic acid peeling + 5% 5-FU solution, indicating an 85.7% reduction in the number of AK in the limbs treated with 5-FU cream. 24 The smaller sample size of the aforementioned study, the treatment area including the hands, as well as the different doses, which may interfere with adherence to treatment, are characteristics that may explain the slightly favorable difference in relation to the 75% reduction in AK count found in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…When comparing online recruitment to traditional offline recruitment strategies, online strategies appear more time-efficient. Our review of the published literature on AK from the past 10 years highlighted the time efficiency of an online recruitment approach for RCTs in dermato-oncology ( Table 2 ) [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. A review by Jacques RM et al of the recruitment rates using conventional strategies in 388 RCTs between 1997 and 2020 found that the median patient recruitment rate per site was 0.95 per month (0.03 per day) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%